The power of logic - Frances Howard-Snyder; Daniel Howard-Snyder; Ryan Wasserman (New York, New York : McGraw Hill Education, 2020)
Through a direct and accessible writing style and engaging samples and exercises, The Power of Logic provides an introduction to information logic, traditional categorical logic, and modern symbolic logic while giving students the opportunity to apply their critical thinking skills to interesting arguments
Keywords: Logic Textbooks